2010
DOI: 10.2478/v10098-010-0024-y
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction of dense fine-grained slurries

Abstract: Attractive and repulsive forces acting in the slurry due to different ions absorbed on surface of fine particles, especially colloidal ones, strongly affect the flow behaviour of highly concentrated fine-grained slurries. The attractive forces between the fine-grained solid particles initiate the coagulation process, which gives rise to voluminous aggregates where a large amount of water is fixed. A modification of the physicalchemical environment of the slurry by addition of a peptizing agent produces repulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…9 Viscosity and shear stress of slurry could be decreased by adding different additives, thereby enhancing the possibilities of a high percentage of solids in the slurry transportation. 10 Many investigators have examined the effects of various additives on the rheological behavior of fly ash slurry at high concentrations during pipeline transportation. A substantial reduction in the viscosity of the slurry was observed by using 0.1% sodium hexametaphosphate by mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Viscosity and shear stress of slurry could be decreased by adding different additives, thereby enhancing the possibilities of a high percentage of solids in the slurry transportation. 10 Many investigators have examined the effects of various additives on the rheological behavior of fly ash slurry at high concentrations during pipeline transportation. A substantial reduction in the viscosity of the slurry was observed by using 0.1% sodium hexametaphosphate by mass.…”
Section: Introductionmentioning
confidence: 99%
“…The flow behavior of fly ash slurry depends on different factors, for instance, shape of particles, particle size distribution, solid concentration in slurry, and slurry viscosity . Viscosity and shear stress of slurry could be decreased by adding different additives, thereby enhancing the possibilities of a high percentage of solids in the slurry transportation . Many investigators have examined the effects of various additives on the rheological behavior of fly ash slurry at high concentrations during pipeline transportation.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the larger particle size distribution of desulfurization gypsum. Some studies have reported that the introduction of coarse particles will reduce the attraction between the particles in the paste, and lead to the destruction of the aggregates formed by the ultrafine particles, thereby reducing the viscosity of the paste [24]. Therefore, desulfurized gypsum is helpful to improve the fluidity of the paste.…”
Section: Fluiditymentioning
confidence: 99%
“…Study indicates that additives of different nature help reduce the values of viscosity and shear stresses of slurry, thus improving flow behaviour and creating a good chance to increase the percentage of solid parts in slurry (Vlasak et al, 2010). In literature, reports have been made on the effects of various additives on rheological properties of the FA slurry at high concentrations (Chandel et al, 2009a;Mosa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%